1992
DOI: 10.1007/bf00232957
|View full text |Cite
|
Sign up to set email alerts
|

Organelle DNA polymorphism in apple cultivars and rootstocks

Abstract: Restriction fragment length polymorphisms (RFLPs) have been used to detect chloroplast (cp) and mitochondrial (mt) DNA variation among 18 apple cultivars and three rootstocks. The distribution of RFLP patterns allowed the assignment of these genotypes into three groups of cytoplasmic relatedness. Our results also demonstrate maternal inheritance of cp- and mtDNAs in apple. Thus, the organelle DNA assay provides a convenient and reliable method to assess cytoplasmic diversity within the apple germ-plasm collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…Probably, sago palm from Papua moved to Sumatra which carried out by people when they moved from Papua to Sumatra in the past and formed a new population in the new places. This prediction may occur because RAPD markers which used did not show as conservative as cpDNA markers which uniparental inherited (Ishikawa et al, 1992;Savolainen et al, 1995). RAPD markers are molecular nuclear genome which related with DNA recombinant process and biparentally inherited (Viard et al, 2001).…”
Section: A 6bmentioning
confidence: 97%
See 1 more Smart Citation
“…Probably, sago palm from Papua moved to Sumatra which carried out by people when they moved from Papua to Sumatra in the past and formed a new population in the new places. This prediction may occur because RAPD markers which used did not show as conservative as cpDNA markers which uniparental inherited (Ishikawa et al, 1992;Savolainen et al, 1995). RAPD markers are molecular nuclear genome which related with DNA recombinant process and biparentally inherited (Viard et al, 2001).…”
Section: A 6bmentioning
confidence: 97%
“…In our observation showed that the different genetic markers used did not change grouping pattern of sago palm. Some cases in the molecular analysis, the dissimilarities grouping pattern, by using the same markers or different markers, were found frequently in the studied of genetic relationships (Ishikawa et al, 1992;Viard et al, 2001;Panda et al, 2003). …”
Section: Genetic Relationships In the Level Of Individualsmentioning
confidence: 99%
“…Papua could be the origin and center of sago palm diversity because it has the highest specific haplotypes and the highest numbers of haplotypes, as well as the existence of wild types. Haplotypes described in this study must have existed in the distant past because cpDNA markers exhibit highly conservative sequences (Provan et al 2001), very low mutation rates which range from 3.2 × 10 −5 to 7.9 × 10 −5 (Provan et al 1999), and no recombinant DNA (Ishikawa et al 1992;Provan et al 2001) and are uniparentally inherited (Savolainen et al 1995;Viard et al 2001). The highest numbers of haplotypes indicate the highest variation as occurred in populations of Abies alba Mill.…”
Section: Haplotype Identification and Compositionmentioning
confidence: 73%
“…Four apple cytoplasmic groups were differentiated by polymorphisms detected with mitochondrial cox1 and atp9 gene probes (Ishikawa et al 1992;Kato et al 1993a): Golden Delicious type, Delicious type, McIntosh type, and Dolgo Crab type. A large number of European, the US and Canadian ancient cultivars are placed in Golden Delicious, Delicious, and McIntosh types, whereas Chinese crab apples are included in either Delicious or Dolgo Crab type.…”
Section: Mitochondrial Dna Polymorphismmentioning
confidence: 99%
“…Due, in part, to uniform cytoplasm types, it is to be avoided. Moreover, both chloroplastic (cp) and mitochondrial (mt) DNA polymorphisms might allow maternal lineages to be followed, because in most plant species, including apple, chloroplasts and/or mitochondria are inherited exclusively from the maternal parent (Ishikawa et al 1992;Robinson et al 2001;Harris et al 2002). In apple, cpDNAs and mtDNAs were used to characterise the cytoplasmic diversity within a wide range of germplasm accessions (Ishikawa et al 1992;Kato et al 1993aKato et al ,b, 2012Savolainen et al 1995;Robinson et al 2001;Coart et al 2006;Wakatsuki et al 2011;Kitazaki et al 2013).…”
mentioning
confidence: 99%